2022
DOI: 10.3390/su142113995
|View full text |Cite
|
Sign up to set email alerts
|

The Medium-Term Impact of the COVID-19 Pandemic on Population Dynamics: The Case of Italy

Abstract: The COVID-19 pandemic has caused an abrupt break in economic, demographic and social dynamics, both in developing countries and advanced economies, perhaps with a more significant impact in the latter, though further evidence is needed to support this assumption. Unfortunately, earlier research on medium- and long-term impacts of the pandemic on urban and regional systems—with particular reference to the demographic dimension—have not yet reached a consensus on methodological and operational approaches. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Selection of a restricted number of non-redundant indicators relevant to this study was based on an early study by Alaimo et al ( 2022a ) that focused on the main changes in population dynamics affecting the demographic balance, and additional demographic phenomena possibly influenced by COVID-19 pandemic in the medium-term (Fiore et al 2020 ). Population balance indicators made available for each year of investigation include: (1) crude birth rate, (2) crude death rate, (3) the consequent natural balance (births–deaths), calculated as a percent rate of native population growth, (4) internal migration rate, (5) foreign migration rate, representative of the net migration balance (immigrants–emigrants), calculated as the percent rate of non-native population growth and, finally, (6) population annual growth rate (%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of a restricted number of non-redundant indicators relevant to this study was based on an early study by Alaimo et al ( 2022a ) that focused on the main changes in population dynamics affecting the demographic balance, and additional demographic phenomena possibly influenced by COVID-19 pandemic in the medium-term (Fiore et al 2020 ). Population balance indicators made available for each year of investigation include: (1) crude birth rate, (2) crude death rate, (3) the consequent natural balance (births–deaths), calculated as a percent rate of native population growth, (4) internal migration rate, (5) foreign migration rate, representative of the net migration balance (immigrants–emigrants), calculated as the percent rate of non-native population growth and, finally, (6) population annual growth rate (%).…”
Section: Methodsmentioning
confidence: 99%
“…Response to the intrinsic shock has been demonstrated to be more or less rapid depending on the specific process (Ullah et al 2020 ; De Rose et al 2021 ; Thomas et al 2022 ). Short-term, medium-term, and long-term effects can finally differ and literature evidence is still occasional, since only short-term impacts have been investigated with some details (Aassve et al 2021 ; Dumont 2021 ; Alaimo et al 2022a ; Bailey et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This creates tensions between institutions and policies, potentially giving rise to conflicts and institutional change. Moreover, recent studies have shown that the COVID-19 pandemic [39] has created a shock to institutional structures, culminating in significant policy changes-and likely more-across the globe [39][40][41][42]. This unforeseen and abrupt disruption has compelled governments to enact new policies and regulations in order to address the health and economic repercussions of the pandemic [43].…”
Section: 'Historical Institutionalism' and 'Neo-institutionalism' As ...mentioning
confidence: 99%
“…Despite these positive aspects, some native citizens remain skeptical of the impact of immigrants on urban economies (Alaimo et al, 2022;Zekovic & Maricic, 2020). Some argue that immigrants take jobs away from native citizens and depress wages (Lazaridis & Romaniszyn, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%